An investigation of consumer willingness to pay for traceable pork accompanied by supplementary quality assurance information - Zengjin Liu; Tingting Fan; Caixia Li; Shanshan Wang (Frontiers in Sustainable Food Systems)
IntroductionWith increasing consumer concern regarding food safety, willingness to pay (WTP) for food has become a significant focal point of research. This study explored consumer willingness to pay for traceable pork in Shanghai with additional quality credit information.MethodsIn October of 2020, 669 valid respondents were surveyed across 15 urban districts in Shanghai. By employing the contingent valuation method and a binary logit model, we empirically analyze consumer WTP for credit-traceable pork and its influencing factors, and estimate the average WTP.ResultsThe results indicate the following. (1) As bid prices increase, fewer consumers are willing to pay extra for credit-traceable pork. Specifically, 94.59% of the consumers were willing to pay an additional price when the bid price was 2 yuan/kg, whereas only 10.53% were willing to pay 30 yuan/kg. (2) Nine variables significantly influence consumer WTP for credit-traceable pork: bid price, purchase experience, trust level, concern for pork, confidence in pork, purchasing from specialty stores, local pork purchasing habits, gender, and education level. On average, consumers are willing to pay an additional 8.48 yuan/kg for credit-traceable pork compared with regular pork. Although certain variables do not exhibit a significant impact, the WTP for credit-traceable pork varies considerably among different consumer groups.DiscussionBased on these findings, we propose strategies to expedite the development of a credit traceability system for agricultural products.